2012
DOI: 10.1074/jbc.m112.385831
|View full text |Cite
|
Sign up to set email alerts
|

Post-translational Modification of Serine/Threonine Kinase LKB1 via Adduction of the Reactive Lipid Species 4-Hydroxy-trans-2-nonenal (HNE) at Lysine Residue 97 Directly Inhibits Kinase Activity

Abstract: Background: LKB1 is a key signaling kinase that regulates cellular growth. Results: The reactive aldehyde 4-hydroxynonenal (HNE) forms adducts on LKB1 that directly inhibit kinase activity. Conclusion: Oxidative modification at Lys-97 by HNE is sufficient for inhibition of LKB1. Significance: This work describes how a key growth suppressor protein is inactivated during states of oxidant stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 39 publications
0
20
2
Order By: Relevance
“…Dolinsky et al first reported that HNE (40 μM) could conjugate with LKB1 and repress its activity, and inhibit its downstream substrate AMPK activity, and thus result in the activation of mTOR/p70S6 kinas pathway in isolated cardiomyocytes [95]. This finding was supported by other studies, which demonstrated that LKB1 was inhibited by HNE in various cell models, including primary mouse cardiomyocytes (20 μM) [96], HEK293T cells (1–40 μM) [97], and rat ventricular cardiomyocytes (10 μM) [98]. In these studies, HNE-LKB1 adducts were detected and total LKB1 decreased, and this was postulated as the mechanism of LKB1 inhibition.…”
Section: Aging-related Signaling Pathways Affected By Hnementioning
confidence: 80%
“…Dolinsky et al first reported that HNE (40 μM) could conjugate with LKB1 and repress its activity, and inhibit its downstream substrate AMPK activity, and thus result in the activation of mTOR/p70S6 kinas pathway in isolated cardiomyocytes [95]. This finding was supported by other studies, which demonstrated that LKB1 was inhibited by HNE in various cell models, including primary mouse cardiomyocytes (20 μM) [96], HEK293T cells (1–40 μM) [97], and rat ventricular cardiomyocytes (10 μM) [98]. In these studies, HNE-LKB1 adducts were detected and total LKB1 decreased, and this was postulated as the mechanism of LKB1 inhibition.…”
Section: Aging-related Signaling Pathways Affected By Hnementioning
confidence: 80%
“…LKB1 can phosphorylate downstream AMPK at threonine 172 (30)(31)(32). Metformin, phenformin and AICAR are activators of AMPK (4,(33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…While prior studies have used HNE concentrations of 40 uM [21] and higher [27] in cardiac myocytes, our previous work has shown that an HNE concentration as low as 10 μM inhibits LKB1 activity through the formation of HNE-adducts [28]. Therefore, cultured adult rat ventricular cardiac myocytes (ARVMs) were treated with 10 μM HNE for 1 hour or Norepinephrine (NE) as a positive control, and the cells were incubated with [ 3 H]-leucine for 24 hours.…”
Section: Resultsmentioning
confidence: 99%